Liensinine can improve vascular remodeling in hypertension through the ferroptosis-related TLR4 inflammatory pathway - Daxin Chen; Peizhi Jia; Meiling Wang; Baojie Du; Haitao Du; Xi Huang; Jianwei Zeng; Qiaoyan Cai; Ling Zhang; Ying Zhu; Shan Lin; Dawei Lian; et al. (Journal of Molecular Medicine, 2026)

Landsat observation reveals upward trend of surface water temperature in the Three Gorges Reservoir over the past quarter century: divergent effects of climate changes and dam constructions - Han Peng; Botian Zhou; Dongmin Wang; Yue Yuan; Guang Li; Meiling Liu; Ling Wu; Mingsheng Shang (Journal of Oceanology and Limnology, 2026)

An NSGA-III–based predict–optimize–evaluate framework for low carbon land use optimization: A case study of the Yangtze River Delta - Menglin Yu; Jie Tao; Peng Zhang; Meiling Zhou; Beiying Huang; Jie Guo; Jialin Yi (Journal of Environmental Management, 2026)

Synergistic T cell and microbiome dysregulation in FOXP3-mediated immune enteritis: insights from multimodal omics - Meiling Jin; Cheng Jin; Shunlai Shang; Yuqing Gu; Peng Jin; Haibin Yu; Diangeng Li (Science China Life Sciences, 2026)

Removal of organochlorine from the oil phase by poly(BMA-co-SMA-co-DAP) acrylic resin: Adsorption selectivity, kinetics, thermodynamics, molecular simulation and DFT calculations - Pan Luo; Xi Deng; Yingchun Lu; Meiling Li; Guihong Lan; Haiyan Qiu; Bo Xu; Yinli Peng (Journal of Environmental Chemical Engineering, 2026)

Hydrangea-derived nitrogen-doped carbon dots: A dual-purpose platform for on-site chlortetracycline detection and time-limited anti-counterfeiting - Meiling Long; Decheng Peng; Jun Yang; Shaogui Wu (Analytica Chimica Acta, 2026)

Global distribution of the terrestrial moisture dynamics response to the meteorological dry-wet abrupt alternation - Jianyu Fu; Mingzhu Cao; Yang Lu; Chunzhu Wei; Xuejin Tan; Meiling Zheng; Liqian Peng; Wenhao Jia; Bingjun Liu (Journal of Hydrology, 2026)

Genetic context-dependent regulation of FlbE enhances morphology modulation and citric acid production in Aspergillus niger - Meiling Chen; Xiaomei Zheng; Peng Du; Xiaomeng Ni; Zhimin Li; Ping Zheng; Jibin Sun (Bioresource Technology, 2026)

Solar-driven superhydrophobic modified polyurethane sponge for rapid in-situ recovery of oil and microplastics in marine oil spill co-contamination - Chuanliang Zhao; Sidan Peng; Bo Wu; Le Kang; Lanlan Liang; Meiling Liu; Liwei Yang; Wendong Wang; Xing Xu (Journal of Hazardous Materials, 2025)

Manufacture of a fluorescent covalent organic framework and its Eu3 + -functionalized material for the design of dual-functional platforms for fluorescent and colorimetric sensing - Yuqiang Xiao; Jiaqi Hu; Mingyue Wang; Yue Lan; Dandan Wang; Famin Ke; Lingling Li; Minmin Wang; Leijiao Peng; Meiling Yang; Tianzhen Gao; Jianming Wu; et al. (Journal of Environmental Chemical Engineering, 2025)

PPAR γ changing ALDH1A3 content to regulate lipid metabolism and inhibit lung cancer cell growth - Xinyuan Tian; Xiaoping Bai; Yunqi Han; Yu Ye; Meiling Peng; Hongwei Cui; Kai Li (Molecular Genetics and Genomics, 2025)

EDIL3 induced by GLIS2 suppresses the anti-tumor activity of CD8+ T cells and expedites epithelial-mesenchymal transition in thyroid cancer - Xu Qian; Bo Fu; Shuangfu Peng; Meiling Xue; Zhaohui Zhu; Dan Yao (Journal of Molecular Histology, 2025)

One stone, several birds: A carboxyl-carbazole-rich fluorescent covalent organic framework for the detection of tetrabromobisphenol S, Fe³ ⁺, ascorbic acid, D/L-arginine, and the removal of tetrabromobisphenol S - Jiaqi Hu; Mingyue Wang; Min Wang; Dandan Wang; Yuqiang Xiao; Yue Lan; Lingling Li; Meiling Yang; Minmin Wang; Leijiao Peng; Famin Ke; Xiurong Guo; et al. (Journal of Hazardous Materials, 2025)

Nanoplastics in infusion system remains underexplored: Evidence from detected nanoplastics in hospital-sourced infusion products - Licheng Wang; Jing Peng; William Ji; Muhammad Ali Tahir; Jilun Wang; Tao Wang; Meiling Weng; Liwu Zhang (Journal of Hazardous Materials, 2025)

Tamoxifen regulates ferroptosis of hepatocytes by targeting SLC1A5 to activate hepatic stellate cells and liver fibrosis - Sha Shi; Meiling Zhang; Chengkai Zhu; Shanhao Zhu; Jie Yu; Qi Sui; Jiaqi Xu; Juan Ren; Jingnan Zhang; Peng Chen; Yi Zhang (Chemico-Biological Interactions, 2025)

Comparison of Meltpro Myco Assay with MALDI-TOF Mass Spectrometry for rapid and accurate detection of clinical Mycobacterium Species - Kehao Peng; Liuyue Xu; Xuezhi Wang; Jianming Hong; Gengchen Zhang; Yuchuan Zhao; Yinong Ye; Zengqi Huang; Jinmei Zhang; Yuchun Huang; Zhiqiao Wu; Xiaolin Yu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Spatial distribution and risk assessment of microplastics in surface sediments in semi-enclosed waters: a case study of Laizhou Bay - Xuzhen Zhang; Hongxian Chu; Meiling Yin; Yadong Liu; Peng Chen; Qiangqiang Zhang; Xuejian Dai; Linghao Kong (Frontiers in Marine Science, 2025)
Marine ecosystems are the most important sinks for microplastics (MPs) from inland sources, and the input of large quantities of MPs into the oceans poses a serious threat to marine organisms and ecosystems. However, the characteristics of MPs contamination and its risk in semi-enclosed seas remain poorly understood. In this research, we conducted a comprehensive analysis and evaluation of the distribution patterns and ecological risks related to MPs found in the surface sediments of Laizhou Bay. We gathered surface sediments from various locations within the bay, which were then processed and analyzed to assess the MP content. According to the results, MPs in Laizhou Bay were widely distributed, with abundances ranging from 36–2125.5 items/g d.w. at different points, with an average of 534.7 items/g d.w. The MP forms were mainly fragments (61.91%) and particles (37.45%), with polyamide (PA) (32.73%), polyethylene terephthalate (PET) (12.42%), and polyurethane (PU) (10.81%) being the most dominant polymer types. MPs mainly originated from marine aquaculture, fishing, and domestic plastic waste; the contribution from marine activities was higher than that from land-based inputs, and their migration and dispersion were mainly affected by the hydrodynamics of water body exchange and intra-bay circulation. According to the pollution load index, the risk index of MPs in Laizhou Bay ranged from 1 to 7.68, indicating a low pollution level. However, the polymer risk index indicated that microplastic pollution in Laizhou Bay was at high risk, and PU and polyvinyl chloride were identified as the primary high-risk sources. This study systematically analyzed the composition, distribution, and multiple source characteristics of MPs in Laizhou Bay. The ecological risks associated with these MPs were assessed through the analysis of pollution load and polymer risk indices. This research offers a valuable dataset and a scientific foundation for understanding and managing MP pollution in semi-enclosed marine environments.

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Towards robust partial nitrification in low-ammonia wastewater: Electrospinning nanofiber composite-enhanced hydrogel beads immobilized comammox Nitrospira - Peng Tang; Liangang Hou; Meiling Yin; Feng Huang; Zhengwei Pan; Tianhao Shi; Jun Li; Yuhan Zhu; Xin Zhang; Peng Gao (Bioresource Technology, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Toxicokinetic insights into distinct mechanisms of action of two thyroid toxicants: Propylthiouracil and pregnenolone 16α‑carbonitrile - Naïs Clavel Rolland; Bénédicte Kiehr; Meiling Zhu; Chun Chen; Peng Gao; Thierry Pourcher; Olivier Blanck (Toxicology and Applied Pharmacology, 2025)

Unraveling the trisubstrate-triproduct reaction mechanisms of wine grape VvCYP76F14 to improve wine bouquet - Zhizhong Song; Meiling Tang; Huilin Xiao; Houhua Xu; Matthew Shi; Adeeba Dark; Zhenqiang Xie; Bin Peng (Food Chemistry, 2025)

Divergent trends in vegetation greenness and resilience across China's forestry ecological engineering regions - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Ecological Engineering, 2025)

The design of novel lithium salt additives: 4-benzonitrile-1,3-double (trimethylboric acid) lithium (LBTA) to endow inherent superior stability in high voltage lithium ion batteries - Lucheng Li; Meiling Liu; Peng Yang; Wenfeng Yuan; Jun Chen (Chemical Engineering Journal, 2025)

Ecosystem resilience response to forest fragmentation in China: Thresholds identification - Xinxin Fu; Zhenhong Li; Jiahao Ma; Meiling Zhou; Lili Chen; Jianbing Peng (Journal of Environmental Management, 2025)

Spatiotemporal changes of vegetation in the northern foothills of Qinling Mountains based on kNDVI considering climate time-lag effects and human activities - Lili Chen; Zhenhong Li; Chenglong Zhang; Xinxin Fu; Jiahao Ma; Meiling Zhou; Jianbing Peng (Environmental Research, 2025)

Construct favorable solid electrolyte interphase by applying alternating current discharge during battery formation - Yulong Zhang; Shiyou Li; Meiling Wu; Lijuan Wang; Ning He; Yin Quan; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2025)

Genome Mining Analysis Uncovers the Previously Unknown Biosynthetic Capacity for Secondary Metabolites in Verrucomicrobia - Xue Di; Peng Li; Jingxuan Wang; Vincent Nowak; Shuai Zhi; Meiling Jin; Liwei Liu; Shan He (Marine Biotechnology, 2024)

Surface phosphorylated Li5FeO4 prelithiation additive synergistically improves the air-stability and lithium-ion conductivity - Lei Niu; Meiling Wu; Yulong Zhang; Cankun Gao; Xin Li; Hao Ding; Ning He; Peng Wang; Jiawen Zhang; Jingxuan Yan; Ningshuang Zhang; Dongni Zhao; et al. (Chemical Engineering Journal, 2024)

m6A-mediated HDAC9 upregulation promotes particulate matter-induced airway inflammation via epigenetic control of DUSP9-MAPK axis and acts as an inhaled nanotherapeutic target - Yingying Zeng; Xin Bai; Guiping Zhu; Mengchan Zhu; Wenjun Peng; Juan Song; Hui Cai; Ling Ye; Cuicui Chen; Yuanlin Song; Meiling Jin; Xue-Qing Zhang; et al. (Journal of Hazardous Materials, 2024)

A new method of alkalinity remediation for Cd-contaminated groundwater by PAAS-modified MgCO3/Mg(OH)2 colloid - Bowen Li; Meiling Tang; Peng Wang; Shibin Liu; Meng Yao; Jun Dong (Chemosphere, 2024)

Subchronic co-exposure of polystyrene nanoplastics and 3-BHA significantly aggravated the reproductive toxicity of ovaries and uterus in female mice - Guanghua Xiong; Haiyan Zhang; Yulin Peng; Huangqi Shi; Meiling Han; Tianle Hu; Hongcheng Wang; Shangrong Zhang; Xiaoqing Wu; Gaoxiao Xu; Jun'e Zhang; Yong Liu (Environmental Pollution, 2024)

Synchronized achieving amount reduction and efficiency increase of lithium salt-type additive by alternating current pulse discharge technology - Shiyou Li; Yulong Zhang; Shumin Wu; Yin Quan; Meiling Wu; Peng Wang; Dongni Zhao; Xiaoling Cui (Chemical Engineering Journal, 2024)

In situ hydrodeoxygenation of heavy bio-oil using a Ce/Fe-based oxygen carrier in methanol-zero valent aluminum media - Meiling Yang; Guozhang Chang; Weiwei Cui; Peng Ni; Qiujie Yi; Laishun Yang; Cuiping Wang (Chemosphere, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Long-term performance of ZVI-stimulating anaerobic/aerobic system - PEI modified ceramic membrane SMBR in reusing food wastewater for irrigation: An industrial project and microbial community shift - Chunyan Wang; Leyong Jiang; Meiling Hu; Cong Wang; Yongzhen Peng; Shujun Zhang; Weikang Qi (Journal of Water Process Engineering, 2023)

Decomplexation of Ni-EDTA enhanced by Fe(III) reduction in the Fenton reaction: Insight into the role of carbonyl groups - Meiling Chen; Lin Ding; Shijun Zhu; Xiuqin Xiong; Xinkai Yuan; Yanhua Peng; Liming Yang; Hui Shi; Penghui Shao; Xubiao Luo (Journal of Environmental Chemical Engineering, 2023)

A new S-scheme heterojunction of 1D ZnGa2O4/ZnO nanofiber for efficient photocatalytic degradation of TC-HCl - Wenhui Chen; Tianxin Kang; Fenqi Du; Peipei Han; Meiling Gao; Peng Hu; Feng Teng; Haibo Fan (Environmental Research, 2023)

Design and synthesis of peptide-drug conjugates to double target EGFR - Xiaozhuo Tan; Meiling Le; Haiwen Wang; Bitao Huo; Tiantian Yu; Peng Huang; Tiangang Luan; Shijun Wen (Phytochemistry Letters, 2023)

Decomplexation of Ni-EDTA by thermally activated persulfate: Efficiency and mechanism - Xinkai Yuan; Wei Xiong; Yanhua Peng; Bo Li; Jianzhi Zhang; Meiling Chen; Xiuqin Xiong; Liming Yang; Hui Shi; Xubiao Luo; Penghui Shao (Journal of Water Process Engineering, 2023)

Negatively regulation of MAVS-mediated antiviral innate immune response by E3 ligase RNF5 in black carp - Jun Yan; Guoxia Qiao; Enhui Wang; Yuqing Peng; Jiamin Yu; Hui Wu; Meiling Liu; Jiagang Tu; Yongan Zhang; Hao Feng (Fish & Shellfish Immunology, 2023)

North-south differences in hypoxia and nitrogen cycle of the East China Sea over the last century indicated by sedimentary bacteriohopanepolyols - Meiling Yin; Jinming Song; Liqin Duan; Huamao Yuan; Xuegang Li; Quancai Peng (Chemical Geology, 2023)

Research progress on antidiabetic activity of apigenin derivatives - Jingyi Jiang; Ting Tang; Yaling Peng; Meiling Liu; Qianwen Liu; Pengbing Mi; Zehua Yang; Hongfei Chen; Xing Zheng (Medicinal Chemistry Research, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Study on the Law of Earth’s Surface Movement on Ultra-Long Working Face - Peng Rui; Fang Meiling; Ren Ruile; Zhu Jianming; Zhao Qifeng; Ouyang Zhenhua (Geotechnical and Geological Engineering, 2022)

Natural population re-sequencing detects the genetic basis of local adaptation to low temperature in a woody plant - Yanmin Hu; Xianjun Peng; Fenfen Wang; Peilin Chen; Meiling Zhao; Shihua Shen (Plant Molecular Biology, 2021)

Safety Analysis Control Measures of Multiple Mining Soft Rock Roadways - Rui Peng; Meiling Fang; Ruile Ren; Qifeng Zhao; Hanwen Jia (Geotechnical and Geological Engineering, 2021)

Retraction Note to: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng‑Jin Guo (Histochemistry and Cell Biology, 2020)

Investigation of Lactic Acid Bacteria Isolated from Giant Panda Feces for Potential Probiotics In Vitro - Qian Liu; Xueqin Ni; Qiang Wang; Zhirong Peng; Lili Niu; Meiling Xie; Yicen Lin; Yi Zhou; Hao Sun; Kangcheng Pan; Bo Jing; Dong Zeng (Probiotics and Antimicrobial Proteins, 2019)

Assessment of debris inputs from land into the river in the Three Gorges Reservoir Area, China - Jing Wan; Yonggui Wang; Meiling Cheng; Bernard A. Engel; Wanshun Zhang; Hong Peng (Environmental Science and Pollution Research, 2018)

Triassic ore-bearing and barren porphyries in the Zhongdian Arc of SW China: implications for the subduction of the Palaeo-Tethys Ocean - Peng Wang; Guochen Dong; M. Santosh; Xuefeng Li; Meiling Dong (International Geology Review, 2017)

Accumulation of intact sulfur mustard in adipose tissue and toxicokinetics by chemical conversion and isotope-dilution liquid chromatography–tandem mass spectrometry - Bin Xu; Cheng Zong; Yajiao Zhang; Tianhong Zhang; Xiaoying Wang; Meiling Qi; Jianfeng Wu; Lei Guo; Peng Wang; Jia Chen; Qin Liu; Hua Xu; et al. (Archives of Toxicology, 2017)

Genome-wide survey and expression analysis of the calcium-dependent protein kinase gene family in cassava - Wei Hu; Xiaowan Hou; Zhiqiang Xia; Yan Yan; Yunxie Wei; Lianzhe Wang; Meiling Zou; Cheng Lu; Wenquan Wang; Ming Peng (Molecular Genetics and Genomics, 2016)

RETRACTED ARTICLE: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng-Jin Guo (Histochemistry and Cell Biology, 2014)

Mining EST-Derived SSR Markers to Assess Genetic Diversity in Cassava (Manihot esculenta Crantz) - Meiling Zou; Zhiqiang Xia; Peng Ling; Yang Zhang; Xin Chen; Zusheng Wei; Weiping Bo; Wenquan Wang (Plant Molecular Biology Reporter, 2011)